A new form of equivalent stress for combined axial–torsional loading considering the tension–compression asymmetry of polymeric materials. Issue 89 (27th September 2015) - Zhang, Jianwei; Jiang, Han; Kang, Guozheng; Jiang, Chengkai; Lu, Fucong
<x xml:space="preserve">Abstract</x> A concise form of equivalent stress which considers the tension–compression asymmetry of polymeric materials is proposed. It is more suitable for combined axial–torsional loading.